2013
DOI: 10.1080/00140139.2013.777798
|View full text |Cite
|
Sign up to set email alerts
|

A study of breast motion using non-linear dynamic FE analysis

Abstract: To facilitate a theoretical analysis of breast motion to enable the design of more supportive bras, a dynamic FEM based on reliable non-linear properties of breast tissues has been developed. The methods and findings have potential widespread benefit for developing new products to promote women's health and comfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…All this evidence suggests that the viscous phase may become a biomarker for the characterization of microstructural changes [123][124][125][126][127]. Table 2 shows some indications of the current status of this parameter in terms of limitations and characteristics that have been specified for some ultrasound elastography methods.…”
Section: Viscoelasticitymentioning
confidence: 99%
“…All this evidence suggests that the viscous phase may become a biomarker for the characterization of microstructural changes [123][124][125][126][127]. Table 2 shows some indications of the current status of this parameter in terms of limitations and characteristics that have been specified for some ultrasound elastography methods.…”
Section: Viscoelasticitymentioning
confidence: 99%
“…The damping directly affects the magnitude of the displacements and in a small proportion, the vibration frequency. It can be observed that the tendency is to consider the breasts as under-damped systems [25,56,57].…”
Section: Modal Analysismentioning
confidence: 99%
“…With the aim of evaluating the behavior dynamic of the prosthesis model a modal analysis was performed within the frequency range of 0 to 6 Hz. This range was considered because people who walk or run have a frequency of step of 1.5 to 4.5 Hz [25,53]. In the simulation results shown in Figure 13, the prosthesis presented 4 natural frequencies and 4 modal forms.…”
Section: Modal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that one important limitation of their study was the employment of costly imaging techniques, such as MRI, to reconstruct the subject-specific FE breast model. To the best of the authors’ knowledge, only Chen et al ( 2013 ) proposed a FE-based method to simulate non-linear breast motion by using a 3D scanning system in order to avoid high costs deriving from MRI. The research goal consisted in the development of a FE model enabling the surgeon to predict the breast large deformations upon the effect of compressive loading conditions due to mammography plates compression, avoiding expensive imaging acquisition techniques, such as MRI, or complicated customized set-ups, such as photogrammetry systems or body scanners (Chen et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%